Flood Mitigation Strategy Based on Hydrological and Hydraulic Modelling in the Urban Area - Sudiyanto, I Wayan; Molo, Hasanuddin; Azis, Sri Misykat; Fathoni, Ahmad; Amaliah, Rizki (Newinera Publisher, 2025)
The urgency of this research lies in the need for a scientific-based solution in understanding the pattern of runoff and flood inundation to support effective mitigation planning. This study aims to analyze the characteristics of the Tallo River runoff before and after infrastructure development; identify the main factors causing flood inundation in the affected area and develop flood mitigation strategies based on hydrological and hydraulic modeling. The methods used include data collection using 15 years of rainfall data (2010–2024), topographic maps (DEM), and land use information; hydrological analysis by calculating the design flood discharge using the Rational and Nakayasu methods; hydraulic modeling with HEC-RAS 2D flood inundation simulation to understand the pattern of inundation distribution due to increasing runoff discharge; evaluation of the impact of development by comparing the runoff discharge before and after development and identifying its contribution to flood risk and mitigation strategies by compiling technical recommendations such as raising the embankment, improving drainage, and increasing the elevation of the affected area. The results of the study indicate that flooding in the Tallo River is mainly caused by the river's inability to accommodate the runoff discharge and the backwater effect of the urban drainage system. The increase in discharge due to the construction of a shopping center was recorded as very small (0.84 m³/second) and was not significant to the occurrence of flooding. The proposed mitigation strategies include building a 2.5-meter high embankment, increasing drainage capacity, and regulating the elevation of the affected area.